In the dream house eaudiobook A memoir. - Machado, Carmen Maria (HighBridge Audio, 2019)
In the Dream House is Carmen Maria Machado's engrossing and wildly innovative account of a relationship gone bad, and a bold dissection of the mechanisms and cultural representations of psychological abuse. Tracing the full arc of a harrowing relationship with a charismatic but volatile woman, Machado struggles to make sense of how what happened to her shaped the person she was becoming. And it's that struggle that gives the book its original structure: each chapter is driven by its own narrative trope-the haunted house, erotica, the bildungsroman-through which Machado holds the events up to the light and examines them from different angles. She looks back at her religious adolescence, unpacks the stereotype of lesbian relationships as safe and utopian, and widens the view with essayistic explorations of the history and reality of abuse in queer relationships. Machado's dire narrative is leavened with her characteristic wit, playfulness, and openness to inquiry. She casts a critical eye over legal proceedings, fairy tales, Star Trek, and Disney villains, as well as iconic works of film and fiction. The result is a wrenching, riveting book that explodes our ideas about what a memoir can do and be.